Optimizing clinical nutrition practices: impact of a formulary prescription-based nutrition therapy protocol in surgical patients - Xu, Mengying; Mao, Jiaojiao (Frontiers in Nutrition, 2026)
BackgroundParenteral nutrition (PN) is a crucial clinical therapy, particularly in surgical patients. However, due to the complex composition of PN formulations, the inappropriate use of PN remains widespread in clinical practice to date. This study established a formulary prescription-based nutrition therapy protocol and assessed the effectiveness of its implementation.MethodThe formulary prescription-based nutrition therapy program included the development of formulary prescriptions for PN and the establishment of a perioperative nutrition medication pathway based on the formulary prescriptions. To evaluate the effect of this protocol in clinical practice, a before-and-after cohort analysis was performed to compare PN administration modalities hospital-wide and nutrition therapy strategies in targeted surgical (general surgery and thoracic surgery) departments. Patients admitted in hospital with gastrointestinal (GI) cancers and receiving abdominal surgery during the study period were further retrospectively analyzed. Nutrition status of patients was evaluated using the levels of postoperative serum albumin and prealbumin. Recovery time and surgical or nutrition-related complications and were also collated as the clinical outcomes.ResultsThe proportion of all-in-one (AIO) admixture orders increased from 47.2 to 85.2%, while multi-bottle systems (MBSs) decreased from 52.8 to 14.8% (p < 0.01). In targeted surgical departments, the utilization rate of personalized total nutrient admixture (TNA) increased from 54.5 to 79.3% (p < 0.01), and a concurrent shift in the approach of nutrition therapy from total parenteral nutrition (TPN) to supplemental parenteral nutrition (SPN) and total enteral nutrition (TEN). Significant benefits across the spectrum of postoperative outcomes were observed in patients with GI cancers. The average postoperative prealbumin levels were elevated on both postoperative day 3 (POD 3) and postoperative day 5 (POD 5) in the after cohort compared to the before cohort (114.40 ± 41.95 vs. 130.09 ± 38.55 mg/L on POD 3 and 131.45 ± 36.88 vs. 148.02 ± 33.69 mg/L on POD 5). In addition, the after cohort showed shorter duration of postoperative PN therapy (8.2 ± 3.3 vs. 6.3 ± 2.6 days) and shorter length of postoperative hospital stay (14.9 ± 5.1 vs. 12.2 ± 4.2 days). However, there was no significant difference in the incidences of postoperative complications between the two cohorts.ConclusionThe formulary prescription-based nutrition therapy protocol can significantly enhance the rational use of PN drugs hospital-wide, optimize clinical nutrition strategies in the surgical patients, and improve short-term clinical outcomes in the patients undergoing GI cancer surgery.